Peer Tutoring: A Strategy to Help Future Teachers Know and Practice Basic Teaching Skills: La tutoría entre iguales: estrategia para que los futuros enseñantes conozcan y practiquen las funciones docentes básicas (Papeles, 2023)
Introduction: This research was carried out with 24 students enrolled in the B.A. program in language teaching at the Benito Juárez University of Oaxaca, Mexico. The objective was to find out how peer tutoring, method characterized by the creation of pairs of students who teach each other an academic topic, could promote the development of basic teaching skills. To conduct the research, the students, firstly, received training on peer tutoring (TEI) and basic aspects of lesson planning. Then, 12 pairs of students (A and B) were formed following the principle of reciprocal peer tutoring. Methodology: Participant A (tutor), following the TEI criteria, prepared a curricular topic and taught it to his peer B (tutoree), who subsequently performed the same function (tutor B and tutoree A). In the research, a qualitative approach was used, and a focus group was employed to collect the data. All students were part of a focus group at the end of their session as tutors. In total, 12 focus groups of tutors each were realized, which were audio recorded. Results and Discussion: The data was reiteratively analyzed, generating the following emergent themes connected with peer tutoring and basic teaching functions: (i) knowing the content to be taught; (ii) elaborating didactic plans; and (iii) designing didactic material. The results indicated that peer tutoring is an effective strategy for teacher training, since during TEI practices, basic teaching activities such as planning and designing teaching materials are launched. Conclusions: This allows an effective teacher-training.
Keywords: Peer tutoring; teacher training; teaching practice; active learning; professional skills